A system to evaluate and understand routing algorithms - Berón, Mario (2008)
In this communication in the form of poster and demo we intent to present a tool aimed at evaluating and understanding routing algorithms. This application has a powerful environment that allows: to draw graphs and manipulate their components in manual or automatic form; to incorporate routing algorithms; to make experiments, measurement, and performance tests; to understand programs. The tool incorporates mechanisms to make easy the task for building executable files. These characteristics make this tool a versatile and easy evaluation and comprehension system to be used with routing algorithms. Along the paper we will emphasize how we conceived and implemented the system’s interface to satisfy the user’s requirements. Our purpose in the context of Interacçao06 is to demonstrate it!.